A Composite of Two Dimensional GeSe2/Nitrogen‐Doped Reduced Graphene Oxide for Enhanced Capacitive Lithium‐Ion Storage. Issue 36 (17th May 2022) - Han, Lijing; Zhao, Andi; Tang, Jing; Wei, Qiaohua; Wei, Mingdeng
Abstract: A composite of two‐dimensional (2D) GeSe2 nanosheets dispersed on N‐doped reduced graphene oxide (GeSe2 /N‐rGO) is fabricated via a simple hydrothermal method combined with post‐selenization process. The high electronic conductivity and the substantial void spaces of the wrinkled N‐rGO can improve the electrical conductivity of the active material and accommodate the volume evolution of GeSe2 nanosheets during the (de)lithiation processes, while GeSe2 nanosheets can reduce ion diffusion length effectively. Meanwhile, the unique layered structure is beneficial to the contact of the active material and electrolyte, and the reversibility of conversion reaction has also been improved. Furthermore, kinetics analysis reveals a pseudocapacitance‐dominated Li + ‐storage mechanism at high rates. In‐situ X‐ray diffraction analysis discloses that the conversion reaction has played a certain part in Li + ‐storage. Thus, the GeSe2 /N‐rGO composite delivers excellent rate capability and good long‐term stability with a high reversible capacity of 711.0 mA h g −1 after 2000 cycles at 1 A g −1 . Abstract : A composite of 2D GeSe2 /N‐rGO is fabricated via a simple hydrothermal method combined with post‐selenization process, and shows superb rate capability and excellent cycling stability. The electrochemical reaction mechanism is also revealed by the in situ XRD, indicating that the conversion reaction has played a certain part in Li + storage.